Resource rent spillovers to fishers remuneration - Thórólfur Matthiasson; Eyjólfur Sigurdsson (University of Iceland, Institute of Economic Studies (IoES), 2018)
Icelandic fishers operate on a higher wage rate than they might have attained in another profession. There could be a number of reasons for this. Fishers are more likely to be full-time workers than the average worker in the economy. Fishers are away from home and they experience more occupation-related hazards than the average worker. Part of their higher wage is compensation for such differences. We utilize a database consisting of information gathered from official registry data (tax returns, labour market surveys, education attainment and the national person registry) that has earlier been used to calculate return on education to estimate remuneration gains when a person switches from any occupation to fishing, correcting for individual factors and for factors like working hours. Preliminary results indicate that a person enjoys an hourly wage that is 39 to 50% higher than that they could have earned engaged otherwise (considering explanatory variables such as age, education and sex).
Keywords: 330; fishing professions; Salary; economic rent; Iceland; Fischereiberufe; Lohn; Ökonomische Rente; Island